PRECISION OF THE OCTANE NUMBER MEASUREMENT FOR GASOLINE BY PETROLEUM LABORATORIES IN ASEAN COUNTRIES (1999) - Bustani Mustafa (Testing Center for Oil and Gas LEMIGAS, 2000)
A high precision of octane number measurement according to standard measurement and to standard requirement is a must in the refining industry. The ASEAN Council on Petroleum (ASCOPE) Correlation Programme is conducted to obtain the precision of octane number measurement data for gasoline the normally used methods of ASTM D 2699 and IP 239. This programme is participated by 19 petroleum laboratories in ASEAN Countries. The test results of the various participating laboratories are subjected to statistical analysis to determine their average value, variance, standard deviation, and to rejected the outlier values. The Grubb T-Test method was used for the statistical rejection of outliers. This method appears to be quite satisfactory for ASCOPE purpose. The implementation of the Grubb T-Test ensures the laboratory consistency and this in turn will give the buyers or sellers of the gasoline confidence in the quality of the gasoline This paper presents the results of 26 ASCOPE Laboratories Test Correlation Programme for Octane Number Measurement (1999).